Feasibility of In-Situ Aeration of Old Dumping Ground for Land Reclamation - Tong, Huan-Huan; Yin, Ke; Chia, Charles Yong-Han; Ahmad, Omar; Xin, Ling; Wang, Jing-Yuan (Chemical Engineering Department, Syiah Kuala University, Banda Aceh, Indonesia, 2013)
Dumping grounds are characterized by the absence of engineering controls such as base liners and cover layer. Consequently, these dumping grounds present risks for surrounding resources such as soil, groundwater and air. The concern for groundwater contamination by leachate from tropical dumping grounds is heightened due to the greater amounts of rainfall and subsequent infiltration and percolation through the waste mass. The emergent demand for old dumping grounds reclamation drives the need to employ remediation technologies. Generally, in-situ aeration is a remediation method that promotes aerobic conditions in the later stage of dumping ground. It accelerates carbon transfer, reduces remaining organic load, and generally shortens the post closure period. However, high rainfall in tropical areas straitens this technique. For example, pollutants could be easily flushed out and more energy should be required to overcome hydrostatic pressure. Although heavy rainfall could supply sufficient water to the substrate and accelerate degradation of organic matter, it may inhibit aerobic activities due to limited air transfer. The waste characterization from Lorong Halus Dumping Ground (closed dumping ground in Singapore) showed that the waste materials were stabilized after 22 years closure. According to the Waste Acceptance Criteria set by European Communities Council, the waste materials could be classified as inert wastes. One interesting finding was that leachate layer detected was about of 5 - 8 meter depth, which entirely soaked the waste materials. Hence, the reclamation design and operation should be carefully adjusted according to these characters. Lorong Halus Dumping Ground case study can provide a guideline for other tropical closed landfills or dumping grounds.